Theory construction in second language acquisition - Jordan, Geoff (Language learning and language teaching, 2004)
Recently, many SLA researchers have adopted a postmodernist approach which challenges the assumption that SLA research is a rationalist, scientific endeavour. The resulting epistemological arguments, plus problems of theory proliferation, contradicting theories, and theory domain, hinder progress towards a unified theory of SLA. Theory Construction in SLA addresses these problems by returning to first principles; it asks whether there is such a thing as reliable knowledge, what is special about scientific method, and how we can best explain SLA. It is the first book to use the philosophy of sc.